Functional Interrogation of Enhancer Connectome Prioritizes Candidate Target Genes at Ovarian Cancer Susceptibility Loci - Wang, Wei; Song, Fengju; Feng, Xiangling; Chu, Xinlei; Dai, Hongji; Tian, Jing; Fang, Xuan; Song, Fangfang; Liu, Ben; Li, Lian; Li, Xiangchun; Zhao, Yanrui; et al. (Frontiers in Genetics, 2021)
Identifying causal regulatory variants and their target genes from majority of noncoding disease-associated genetic loci is a main challenge in post-GWAS functional studies. Although chromosome conformation capture (3C) and its derivative technologies have been successfully applied to nominate putative causal genes for noncoding variants, many GWAS target genes have not been identified yet. Here we generated a high-resolution contact map from epithelial ovarian cancer (EOC) cells with two H3K27ac-HiChIP libraries and analyzed the underlying gene networks for 15 risk loci identified from the largest EOC GWAS. By combinatory analysis on 4021 fine-mapped credible variants of EOC GWAS and high-resolution contact map, we obtained 162 target genes that mainly enriched in cancer related pathways. Compared with GTEx eQTL genes in ovarian tissue and annotated proximal genes, 132 HiChIP targets were first identified for EOC causal variants. More than half of the CVs involved interactions were over 185 kb in distance, indicating that long-range transcriptional regulation were important mechanisms for GWAS variants function in EOC. We also found that many HiChIP gene targets showed significantly differential expressions between normal ovarian and EOC tumor samples. We have validated one of these targets by manipulating rs9303542 located region with CRISPR-Cas9 deletion and dCas9-VP64 activation experiments and found altered expression of HOXB7 and HOXB8 at 17p31.32. Our study presented a systematic analysis to identify putative target genes for causal variants of EOC, which illuminates in-depth mechanism investigation of noncoding regulatory variants in the etiology and pathogenesis of ovarian cancer.